Assessing the Financial Performance of PT. Astra International Tbk by Analyzing Liquidity and Profitability Ratios - Sabda Dian Nurani Siahaan; Lisandra Junika Farel Situmorang; Helen Enola Loren Hutasoit; Annisa Siregar; Magdalena Pebriani Sitepu (Asian Journal of Applied Business and Management, 2023)
The research objective is to analyze financial ratios consisting of liquidity ratios and profitability ratios in assessing the financial performance of PT. Astra International Tbk. The research method used is secondary data taken from a second source or other agencies such as balance sheets and profit and loss reports. And using data collection methods, namely qualitative methods, in the form of notes and other documentation techniques. The data is taken from the company's annual financial report on the official website www.astra.co.id and the IDX website. Then calculate the ratio of financial liquidity and profitability of the company. After being analyzed with financial ratios, the liquidity ratio has decreased from year to year and the Profitability Ratio has increased from year to year, but according to industry standards the status of the company is still relatively good and its financial condition is still quite healthy.